Implementation of Inclusive Education in Elementary Schools in Balikpapan City: Challenges, Solutions, and Impacts - Firman Firman; Ganjar Ganjar; Tri Astuti Nur’aini (Department of Special Education, 2025)
The goal of implementing inclusive education in schools is to guarantee that every student, including those with special needs, receives a high-quality education. This research seeks to evaluate how inclusive education is being carried out in primary schools (SD) in Balikpapan City, with a focus on the challenges faced, solutions proposed, and the effects on student development. A descriptive qualitative method was employed, utilizing observation, interviews, and documentation techniques. Data analysis followed Miles and Huberman's framework, involving data description, analysis, and drawing conclusions. The findings indicate that inclusive education in Balikpapan City's elementary schools holds significant potential to transform the educational approach for students with special needs in Indonesia. Despite ongoing challenges, with adequate support from schools, the government, and the community, inclusive education can offer equitable and high-quality education to all students. Consequently, the goal of education for all can be realized, allowing students with diverse challenges, including physical, mental, and other limitations, to engage in education.